Venturi-type injection system as a potential H2 mass transfer technology for full-scale in situ biomethanation. (15th July 2018) - Jensen, Mads Bjørnkjær; Kofoed, Michael Vedel Wegener; Fischer, Keelan; Voigt, Niels Vinther; Agneessens, Laura Mia; Batstone, Damien John; Ottosen, Lars Ditlev Mørck
Graphical abstract: Highlights: Data on full-scale in situ biomethanation is presented. H2 consumption was increased at higher injection rates. Headspace recirculation improved H2 consumption. The injector system is easily retrofitted to existing digesters. CFD-modelling revealed bubble size as critical for efficient gas transfer. Abstract: Industrial application of biomethanation is impeded by the slow development of cost effective technologies, which can supply the methanogenic archaea with H2 both effectively and at sufficient rates in large scale. This paper is the first to present developmental work of a H2 mass transfer technology in full-scale, investigating the H2 mass transfer potential of a venturi-type injector through injections of up to 33.5 m 3 H2 into a 1200 m 3 anaerobic digester under normal operation. The venturi system poses a potentially inexpensive system of in situ biogas upgrading, since it is easily installed on already existing anaerobic digesters. Experimental H2 consumption rates increased with H2 injection rates, and was clearly indicated to be limited by the gas-liquid mass transfer rate due to injection of large bubbles. Consumption of the unconverted H2 was increased by recirculation of the headspace gas, but at lower rates due to dilution of H2 with biogas. The incomplete H2 consumption gives the venturi system application in combination with ex situ methanation systems in its present form, but the system must be developed further in order to provide sufficient gas-liquid mass transfer efficiency in order to comprise a stand-alone biogas upgrading system.